Querying XML XQuery, XPath, and SQL/XML in context - Melton, Jim, 1946-; Buxton, Stephen (San Francisco, Calif. : Morgan Kaufmann, 2006)
One-stop shopping: what software developers and architects need to know to master XML querying and retrieval.
XML -- Querying -- Querying XML -- Metadata, an overview -- Structural metadata -- The XML information set (Infoset) and beyond -- Managing XML : transforming and connecting -- Storing : XML and databases -- XPath 1.0 and XPath 2.0 -- Introduction to XQuery 1.0 -- XQuery 1.0 definition -- What's missing? -- XQuery APIs -- SQL/XML -- XML-derived markup languages -- Internationalization : putting the "W" in "WWW" -- Finding stuff.
Includes bibliographical references and index.
Keywords: XML (Document markup language); SQL (Computer program language).; Query languages (computer science); Internet programming; Web sites -- Design; Electronic books